Is home the best place to be old? The changing geography of responsibilities in the care for elderly. - De Lange, Frits (Stellenbosch Theological Journal, 2018)
In this article, the changing geography of care for the elderly in today's society is mapped out in (1) its consequences for the meaning of "home" for frail elderly and (2) for the distribution of care responsibilities. Two current ideas that are criticized are that (1) home is always the best place to be (and therefore also the preferred place to receive care), and (2) that one has stronger ethical obligations to people who live in one's neighbourhood, because of their proximity. Together with the so-called ethics of care, care is considered a fundamental societal practice, and the distribution of caring responsibilities a primary ethical question. Care responsibility, it is argued, is never a natural given, but must be negotiated in every situation and different context anew. In following moral philosopher Robert Goodin, the article concludes that responsibility in long-term relationships between frail parents and adult children not proximity is decisive for assigning responsibility, but the parents' specific vulnerability.